Electronic data management for the Hemochron Jr. Signature coagulation analyzer. - Searles B; Nasrallah F; Graham S; Tozer M; Searles, Bruce; Nasrallah, Fadi; Graham, Susan; Tozer, Michelle (Journal of Extra-Corporeal Technology, 2002)
Point-of-care testing (POC, POCT) laboratory devices are being introduced into operating suites and critical care units in ever increasing numbers. The small, portable devices have gained in popularity because of their ease of use and the rapid availability of test results. POCT is an integral part of extracorporeal technology (ECT). A challenge associated with the growth of POC technology is related to management of the data generated by these devices. In the field of ECT, storing, retrieving, analyzing, viewing and charting quality control (QC) and patient test data generated with POC coagulation instruments is essential. We evaluated a premarket version of data management software developed for the Hemochron Jr. Signature coagulation analyzer, a PC-based software capable of fulfilling our objective. A database comprised of greater than 50 plasma and electronic QC results and greater than 140 patient sample results for ACT, PT, and aPTT tests was transferred from a Hemochron Jr. Signature device to two different PCs, each equipped with Hemochron ReportMaker software supplied by the manufacturer. Data files were transferred directly from the coagulation test unit to the PCs via an RS-232 cable. A variety of charts, reports, and file listings were created from the datasets using the software menus. Transfer of the complete database required less than 5 min. The relative speed and simplicity of the data interface promotes frequent charting of QC data, permitting real-time monitoring and early identification of data trends or values requiring intervention. If a subset of QC data is found to be incomplete, altered, or unacceptable, all patient samples tested during that period can be promptly identified. The software also includes data query tools useful for sorting and selecting specific subsets of patient and QC data. Electronic data management can facilitate compliance with quality control requirements and assist clinicians and laboratory personnel in the collection, storage, and review of quality control and patient test data. In addition, the patient and QC data are readily accessible when necessary for use in risk management assessment, accreditation, or litigation proceedings.